Removal of copper and iron by amidoxime modified poly (Acrylonitrile-g-microcrystalline cellulose) - Abdullah, Mohammad (2021)
Heavy metal ions that not treated from many industries have been severely polluted the environment and can caused serious impact to human health. The discharge of heavy metal effluents into water sources can generate accumulation of toxicity and unwanted contaminants. Hence, proper treatment of heavy metal ions from industrial wastewater is a main environmental pollution concern for consideration. The adsorption process become an alternate approach to eradicate heavy metal ions. This study investigated the polymer-based adsorbent; amidoxime modified poly(acrylonitrile-g-microcrystalline cellulose) that was used to remove selected heavy metal ions (copper, Cu2+ and iron, Fe2+) by adsorption method. The poly(acrylonitrile-g-microcrystalline cellulose) was synthesised by redox polymerisation of acrylonitrile (AN) and microcrystalline cellulose (MCC) monomer and further modified chemically with amidoxime to produce AO modified poly(AN-g-MCC) adsorbent. Then, single batch adsorption experiments for each heavy metal, Cu2+ and Fe2+ were executed at different working conditions such adsorbent dosage, pH, initial metal ion concentrations and soaking time. Besides, batch mode of adsorption for binary heavy metal ions onto AO modified poly(AN-g-MCC) was studied. The synthesised of poly(AN-g-MCC) produced the highest yield (96%) at polymer ratio 93:7 (AN:MCC). The characterisations result of polymerised polymer; Fourier transform infrared (FTIR) confirmed the successful of polymerisation due to the presence of absorption peaks that were assigned to the C≡N and –COOH functional groups on the spectra. Scanning Electron Microscope (SEM) showed the appearance of AN bead onto MCC surface. The thermogravimetric (TG) analysis recommended that the thermal stability of poly(AN-g-MCC) was lower as compared with MCC. The poly(AN-g-MCC) where further chemically altered with hydroxylamine hydrochloride. The FTIR spectra verified the successful conversion of C≡N into amidoxime groups. The microanalysis presented that the overall trend of elemental percentage for AO modified poly(AN-g- MCC) copolymers were increase of nitrogen and hydrogen elements. To further confirm the quantity of amidoxime functional group in modified polymer, the amine capacity test was conducted. The ratio of 93:7 has the highest amount of amine capacity (12.42 mmol/g), followed by 90:10 (11.45 mmol/g) and the low amount of amine capacity at feed mole ratios 95:5 (10.5 mmol/g) and 97:3 (9.75 mmol/g). The single batch system of the adsorption progression for the elimination of Cu2+ and Fe2+ were conducted by varying the pH (2 -12), adsorbent dosage (0.2 – 1.0 g), initial metal ion concentration (50-150 mg/L) and contact time (2-100 minutes). The maximum removal percentage for Cu2+ and Fe2+ were 99.5% and 96.4%, respectively at pH 7. The effect of adsorbent dosage showed the 1.0 g/L of adsorbents, result the highest percentage of Cu2+ (99.8%) and Fe2+ (88.63%) correspondingly. The highest percentage removal of Cu2+ and Fe2+ were 99.5% and 95.8% respectively at 50 mg/L. Meanwhile at 60 minutes the percentage removal become maximum for Cu2+ (89.0%) and Fe2+ (87.5%). The experiment data were examined using equilibrium and kinetic studies. Equilibrium data was well fitted with Freundlich isotherms. The Freundlich isotherms showed good agreement for the adsorption of Cu2+ (R2 of 0.9493) with the maximum adsorption capacities of 120.58 mg/g. The adsorption of Fe2+ also satisfied with Freundlich isotherms (R2 of 0.9558) with maximum adsorption capacities of 235.91 mg/g. In binary system, the effects of adsorbent dosage (0.2-1.2 g), pH (3,5, and 9), initial adsorbate concentration (20-100 mg/L) and contact time (0-100 minutes) on equilibrium adsorption capacity were determined. An increase in adsorbent dosage increased the removal of metal ions in binary system. The Cu2+ and Fe2+uptake was more favourable at pH 9 in binary system. The percentage removal of Cu2+ at 100 mg/L of binary solution was 91.13 %, whereas the Fe2+ ions uptake was only 84.51%. Both heavy metal ions reached their equilibrium at 60 min and after that the removal of heavy metal ions become almost constant. Extended Langmuir model and extended Freundlich model provide a suitable description of the experimental binary data. The comparison of the single and binary isotherms reveals an antagonistic interaction (occurred when the adsorption capacity of an adsorbent reduces in a solution containing other components) between the Cu2+ and Fe2+. In addition, pseudo-second-order model was found suitable for the description of adsorption kinetic for both metal ions onto AO modified poly (ANg- MCC), for both single and binary system, signifying chemisorption between adsorbent and heavy metals molecule. Based on experimental findings, AO modified poly (AN-g-MCC) polymer is a promising functional regenerable adsorbent with high capacity to remove heavy metal (for single and binary system) from liquid environment.